Detection Technology and Prospects of Clinical Application of Circulating Tumor Cells in Pancreatic Cancer - YANG Xiaoying (Editorial Office of Medical Journal of Peking Union Medical College Hospital, 2021)
Pancreatic cancer is one of the highly malignant tumors of the digestive system, and early metastasis is an important reason for its short survival time. Circulating tumor cells (CTCs) are a type of tumor cells that are released into the bloodstream from the primary tumor and/or metastatic sites, which have properties similar to primary tumor cells and are closely related to distant metastasis of tumors. In vitro quantitative detection of CTCs is of great significance in the early diagnosis, auxiliary staging, treatment efficacy, and prognosis evaluation of pancreatic cancer. Here we generally reviewed current research on the CTCs enrichment methods of pancreatic cancer and its application in screening pancreatic cancer and metastasis, and evaluating the prognosis.